A study of the stage memory effect in polymers based on the photoelastic effect - Tian, Yu Long (2014)
In previous studies, 3D surface scanners are often used to study the surface geometry of various specimens while recovery is taking place. While 3D scanners offer clear and precise readings of recovery, the scanning process usually takes a longer time for the surface to be read correctly. For a quicker observation of shape recovery, a new method is being explored and tested out. This report aims to find methods to prove the reliability of using photoelastic effects in studying the shape memory effect of polymers. For the method to be proven reliably, a series of experiments on various materials would be tested out. Through a series of tests, the author would achieve the goal of this report. A result would be classified as good when photoelastic images are able to represent the different rate of stress recovery within the specimen. Through the study of photoelastic effects, 3D printed objects were involved in preparing of the experimental setup. Aside from using 3D printed objects in setting up the experiments, various tests were also setup to further test out the capability of printed objects. The printed objects were setup to observe shape recovery of the printed object. While it was not possible to achieve shape recovery images of the tested PLA specimen, it allows more insight on the properties of printed PLA objects. The findings provided would be able to grant better knowledge for future research works. This report mainly covers the various experiments carried out in studying the reliability of using photoelastic effects in studying shape memory effects.